Use of Intranasal Ketamine in Pediatric Patients in the Emergency Department. Issue 12 (December 2021) - Guthrie, Anne Marie; Baum, Regan A.; Carter, Craig; Dugan, Adam; Jones, Landon; Tackett, Trei; Bailey, Abby M.
Abstract : Objectives: Ketamine is a safe and widely used sedative and analgesic in the pediatric emergency department (ED). The use of intranasal (IN) ketamine in exchange for the administration of intravenous sedatives or analgesics for procedural sedation in pediatric patients is not commonplace. The goal of this study was to evaluate provider perceptions and patient outcomes at varying doses of IN ketamine for anxiolysis, agitation, or analgesia. Methods: From January 2018 to May 2018, we performed a prospective survey and chart review of pediatric patients receiving IN ketamine. The primary outcome was to determine provider satisfaction with using IN ketamine. Secondary objectives included comparing outcomes stratified by dose, adverse events, assessing for treatment failure, and ED length of stay (LOS). As a secondary comparison, patients receiving IN ketamine whom otherwise would have required procedural sedation with intravenous sedatives or analgesics were placed into a subgroup. This subgroup of patients was compared with a cohort who received intravenous sedatives or analgesics for procedural sedation during a similar period the preceding year (January 2017 to June 2017). Results: Of the 196 cases, 100% of the providers were comfortable using IN ketamine. The median overall provider satisfaction was 90 out of 100, the perception of patient comfort was 75 out of 100, and perceived patient comfort was maximized when using doses between 3 and 5 mg/kg. There were 15 (7.7%) patients who experienced ketamine treatment failure. Overall, the rate of adverse events was 6%, but were considered minor [nausea (n = 3; 1.5%), dizziness (n = 2; 1%), and drowsiness (n = 2; 1%)]. No patients required respiratory support or intubation. The mean LOS was 237.9 minutes, compared with those who underwent procedural sedation with an LOS of 332.4 minutes ( P < 0.001). Conclusions: This study demonstrates that IN ketamine was able to provide safe and successful analgesia and anxiolysis in pediatric patients in an ED setting. In addition, providers expressed a high degree of satisfaction with using IN ketamine (90 out of 100) in addition to a high degree of patient comfort during the procedure (75 out of 100). Intranasal ketamine provides an alternative to intravenous medication normally requiring more resource-intensive monitoring. Procedural sedations are resource and time intensive activities that increase ED LOS. Intranasal ketamine used for anxiolysis and analgesia offers the benefits of freeing up resources of staff and monitoring while enhancing overall throughput through a pediatric ED.